2020
DOI: 10.4103/jfmpc.jfmpc_766_20
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and associated factors among children 1-5 years of age in rural area of Haryana, India: A community based cross-sectional study

Abstract: Background: Children under five years of age are most vulnerable to the vicious cycles of malnutrition, disease/infection and resultant disability all of which influence the present condition of a child at the microlevel and the future human resource development of the nation at the macrolevel. Aim: The present study was conducted to estimate the prevalence of undernutrition among under-five children; and to determine the associated factors. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Additionally, this prevalence was higher in comparison to the results of earlier studies. 12 - 15 The findings of the current study revealed an 8% prevalence of severe wasting, which is consistent with the results of the study conducted in Gujarat (6%), 16 Haryana (8%), 13 and with the national average (7.7%). 4 In the current study, the prevalence of stunting (36.7%) was slightly lower than it was for the state (39%) and the region (38.9%).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, this prevalence was higher in comparison to the results of earlier studies. 12 - 15 The findings of the current study revealed an 8% prevalence of severe wasting, which is consistent with the results of the study conducted in Gujarat (6%), 16 Haryana (8%), 13 and with the national average (7.7%). 4 In the current study, the prevalence of stunting (36.7%) was slightly lower than it was for the state (39%) and the region (38.9%).…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Chaudhary and Agrawal, (2019) 18 in Jaipur showed that underweight and stunting were significantly associated with number of siblings, birth order, birth weight, and immunization status while wasting was significantly associated with birth weight and immunization status. A study conducted by Chawla et al, 21 in Haryana showed that underweight was significantly associated with birth weight, birth order, prelacteal feed, exclusive breastfeeding, and introduction of complementary feeding while stunting and wasting was significantly associated with birth weight, prelacteal feed, exclusive breastfeeding, and introduction of complementary feeding. A study conducted by Rehan et al, 20 in Rishikesh showed that stunting and wasting were not significantly associated with birth order, birth weight, and immunization status.…”
Section: Discussionmentioning
confidence: 96%
“…This present study found significant association between undernutrition with intake of iron folic acid tablets during ANC and PNC period, duration of pregnancy, and site of delivery. A study conducted by Chawla et al, 21 in Haryana showed that underweight and stunting was significantly associated with antenatal visits, intake of iron folic acid during pregnancy, and place of delivery while wasting was significantly associated with antenatal visits and intake of iron folic acid during pregnancy. A study conducted by Hossain et al, 22 showed that underweight was not associated with mother's age.…”
Section: Discussionmentioning
confidence: 96%
“…The survey tool was developed based on the review of previous national surveys in India[ 5 6 ] as well as the published literature on child malnutrition. [ 9 10 14 15 ] Respondents included key informant (mother of the respective child) participated in the study. Demographic and socioeconomic details and variable of child and maternal history were sought by interview and by reviewing medical records.…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 ] The nutritional interventions during this period had greatest impact on child health, survival, and development. [ 8 ] Several studies explored prevalence and described associated risk factors of under-five (U5) undernutrition in India[ 9 10 ] and other developing countries,[ 11 12 ] but there is a paucity of literature reporting the prevalence as well as determinants of malnutrition in children less than 2 years of age. The present study was conducted to assess prevalence of malnutrition and to identify the factors related to it among children less than 2 years of age in Devbhumi Dwarka District of Gujarat.…”
Section: Introductionmentioning
confidence: 99%